Desain Dashboard Web untuk Pemantauan dan Pelaporan Status Produksi di PT. Care Spunbond - Ameilia Nurfadhilah; Anis Pitriya; Wahyu Hidayat (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
PT Care Spunbond faces significant challenges in managing production status reports due to its reliance on a manual, paper-based recording system. This results in non-real-time data input, slow data processing, and a high risk of data loss or corruption. To address these issues, this study aims to design a user-friendly, web-based dashboard for monitoring and reporting production status. This system is designed to enable fast data input, provide easy access for the Quality department, and provide secure and integrated data storage. The research method used is a descriptive approach with data collection techniques through observation, interviews, and literature studies. After that, a system analysis was conducted using the PIECES framework to identify existing problems, followed by the design of a UML (Unified Modeling Language)-based system. The results show that the proposed system can improve data processing efficiency, improve report accuracy, and ensure better production data security. With the implementation of this system, the company is expected to accelerate data-driven decision-making, increase transparency, and support efforts to continuously improve product quality.